Copyright Certification of Son Horek Works in East Java: Social Impact and Legal Implications - Utami, Rahayu Sri; Rezki, Moch. Gufron Fajar (Kajian Ilmiah Hukum dan Kenegaraan, 2025)
Purpose: This study examines the legal approval of copyright over Son Horek, a traditional cultural expression originating from indigenous communities in East Java, and analyzes its socio-cultural and legal implications. The research focuses on how the transformation of Son Horek into a commercial product has triggered ownership claims that marginalize indigenous communities as the original collective custodians. Methodology/Approach: This study adopts a juridical-normative and sociological approach. It analyzes Indonesian Copyright Law No. 28 of 2014 and examines its application to traditional cultural works. The research also incorporates socio-legal perspectives to assess the impact of copyright recognition on indigenous communities and their cultural practices. Results/Findings: An imbalance exists between individual legal rights and collective indigenous rights, causing unfair recognition, cultural distortion, and the risk of criminalization. Conclusions: The study reveals a mismatch between individual-based copyright law and the collective nature of Son Horek, thereby marginalizing indigenous communities. Limitations: This study is normative and socio-legal in nature and does not include empirical field surveys or quantitative measurements. Future studies may strengthen the analysis through ethnographic research and participatory methods involving indigenous stakeholders. Contributions: This study contributes to legal and cultural scholarship by offering a critical perspective on the protection of traditional cultural expressions. It emphasizes the need for an inclusive, contextual, and justice-oriented legal framework that integrates the principle of interlegality and strengthens the role of customary institutions in recognizing collective cultural rights.